Rhamnogalacturonan II structure shows variation in the side chains monosaccharide composition and methylation status within and across different plant species. (5th August 2013) - Pabst, Martin; Fischl, Richard M.; Brecker, Lothar; Morelle, Willy; Fauland, Alexander; Köfeler, Harald; Altmann, Friedrich; Léonard, Renaud
Summary: A paradigm regarding rhamnogalacturonans II (RGII) is their strictly conserved structure within a given plant. We developed and employed a fast structural characterization method based on chromatography and mass spectrometry, allowing analysis of RGII side chains from microgram amounts of cell wall. We found that RGII structures are much more diverse than so far described. In chain A of wild‐type plants, up to 45% of thel –fucose is substituted byl –galactose, a state that is seemingly uncorrelated with RGII dimerization capacity. This led us to completely reinvestigate RGII structures of the Arabidopsis thaliana fucose‐deficient mutant mur1, which provided insights into RGII chain A biosynthesis, and suggested that chain A truncation, rather thanl –fucose tol –galactose substitution, is responsible for the mur1 dwarf phenotype. Mass spectrometry data for chain A coupled with NMR analysis revealed a high degree of methyl esterification of its glucuronic acid, providing a plausible explanation for the puzzling RGII antibody recognition. The β–galacturonic acid of chain A exhibits up to two methyl etherifications in an organ‐specific manner. Combined with variation in the length of side chain B, this gives rise to a family of RGII structures instead of the unique structure described up to now. These findings pave the way for studies on the physiological roles of modulation of RGII composition.